Quantifying forest stocking changes in Sundarbans mangrove using remote sensing data - Yaqub Ali; M. Mahmudur Rahman (Science of Remote Sensing)
The Sundarbans, the world's largest mangrove ecosystem, faces significant challenges from forest stocking changes due to natural and anthropogenic factors. Scientific studies on these changes are not available. This study uses remote sensing techniques to quantify long-term changes in mangrove forest canopy height, aboveground biomass (AGB), and forest carbon stocks. Using Shuttle Radar Topography Mission (SRTM) and Global Ecosystem Dynamics Investigation (GEDI) LiDAR data sets, we assessed canopy height and forest stocking changes, and changes in AGB carbon fluxes over the last two decades in the Sundarbans mangrove. Calibrated SRTM data provided tree canopy height (TCH) estimates for 2000, while calibrated GEDI LiDAR data facilitated assessments of TCH for 2023. The findings show substantial changes in TCH, AGB, and carbon stock distribution in the Sundarbans mangrove between 2000 and 2023. TCH in the 5–10 m class notably increased from 58.3% in 2000 to 70.8% in 2023, while TCH above 15 m decreased, and those under 5 m regrew. Higher AGB carbon classes (>50 tons ha⁻1) decreased, with only the lowest class (<50 tons ha⁻1) increased, indicating notable forest carbon stock reduction due to deforestation and forest degradation. Approximately 1571 Kt of AGB carbon were lost over 23 years, which represents around 4% of the total stock. The driving forces of forest stocking changes could be the changes in the dynamic energy balance from the estuarine river system and the tidal waves, relative sea-level change, increases of salinity in various zones of Sundarbans mangrove, other anthropogenic factors, etc. This research provides valuable insights into Sundarbans mangrove dynamics, aiding global forest degradation and forest growth in understanding forest stocking change and their role in terrestrial carbon flux and global climate change. The results will be helpful for the forest manager in identifying the locations where there is forest degradation or enhancement of forest growing stock and planning any silvicultural operations that are needed in the forest. This is also useful for climate change scientists to understand probable man-made or natural driving forces of the changes in forest stocking in the Sundarbans mangrove forests. It underscores the urgency of integrating deforestation and forest degradation into climate strategies for effective carbon management and conservation efforts, that align with carbon sequestration goals, contributing to broader climate change mitigation strategies.